Use of Short-Radius Centrifugation to Augment Ankle-Brachial Indices. (1st June 2009) - Grenon, S. Marlene; Mateus, Jaime; Hsiang, York; Sidhu, Ravi; Young, Laurence; Gagnon, Joel
Abstract : Background: Peripheral arterial disease is mainly caused by atherosclerosis and is characterized by decreased circulation, lower blood pressure, and insufficient tissue perfusion in the lower extremities. The hemodynamics of standing and altered gravity environments have been well studied relative to arm blood pressures but are less well understood for ankle pressures. Methods: Because regional blood pressure depends, in part, on the gravitational pressure gradient, we hypothesized that artificial gravity exposure on a short-arm centrifuge with the center of rotation above the head would increase blood pressure in the lower extremities. Cardiovascular parameters for 12 healthy subjects were measured during exposure to supine short-arm centrifugation at 20, 25, and 30 revolutions per minute (rpm), corresponding to centripetal accelerations of 0.94, 1.47, and 2.11 Gz at the foot level, respectively. Results: Systolic ankle blood pressure significantly increased at all levels of centrifugation. Ankle-brachial indices (the ratio of systolic ankle to arm blood pressures) increased significantly from 1.17 ± 0.03 to 1.58 ± 0.03 at 0.94 Gz ( P < 0.005), 1.74 ± 0.02 at 1.47 Gz ( P < 0.005), and 1.89 ± 0.06 at 2.11 Gz ( P < 0.005). Systolic arm blood pressure significantly increased at 2.11 Gz, but heart rate did not change significantly. All parameters returned to normal after cessation of centrifugation. Conclusions: We demonstrated that short-radius centrifugation leads to an increase in ankle-brachial indices. This could have potential implications for the treatment of peripheral arterial disease.